Prevention of facial overfilled syndrome - Le, Thi Cao Nguyen (Tạp chí Y Dược Huế, 2025)
The rising preference for hyaluronic acid fillers in aesthetic rejuvenation stems from their dual advantage of delivering immediate anti-aging effects and exerting beneficial biological actions with minimal invasiveness. Although the medical advantages of fillers for enhancing appearance and combating the effects of facial aging are widely acknowledged, there have been numerous instances of fillers being used improperly in rejuvenation procedures. The presence of these events can result in enduring consequences that are frequently disregarded during the identification of “Facial overfilled syndrome (FOS)”. Early recognition of FOS is crucial, with key symptoms including a heavy mid-to-lower face, “setting sun” eyes, a broadened nose, a round and over-protruding forehead, and a pointy chin. The review is to describe the anatomy of facial aging, analyze the reasons and symptoms of facial overfill syndrome, and recommend possible treatment choices. Utilizing small-dose point injection techniques or Canula injection techniques guarantees accurate classification and suitable dosage, while also providing early education to clients regarding this issue. It is essential to enhance the safety and aesthetics of patients, avoid the development of facial overfill syndrome, and establish a suitable method for patient rejuvenation. It is crucial to highlight the demand for education in comprehending and mastering filler-based cosmetic operations for physicians.